Location based tourist companion application on Android - Shaji Babu, Saran Babu. (2013)
Tourism is one of the booming and rapidly growing industries in the world. The industry is very important for economic and environmental growth of a country. Countries all over the world are taking various measures to promote their tourism industries and ensure the safety of tourists. Yet there is a steep increase in crimes against tourists all over the world. Even though there are many location based smartphone applications available for tourists, majority of them don’t address the issue of ensuring the safety of tourists. Another issue is, in most of the tourist companion applications user has to browse through the applications to find nearby Places of Interest. It would be useful if applications can provide dynamic alerts about nearby Places of Interests or dangerous places reported with high crime rates. The aim of this project is to create an application in Android platform that will enable users to get location based alerts about nearby Places of Interest; security alerts if the location is risky and create location alarms by specifying locations to notify them when they reach that particular location. Client/Server architecture was used to implement this project. Details regarding Places of Interests and dangerous places are stored in an external database, which are pulled to the application in client device. These details are used to generate location specific alerts. The client side application was implemented using Java and server side using PHP and SQL. Google Maps API and Google Places API were integrated to the project. The implementation also considered factors such as usability, consistence, performance and efficiency.